Analysis of Population Growth and Distribution towards Health Facilities and Infrastructure in Sikakap District Mentawai Islands Regency - Wulansari, Septiyani Kiky; Hermon, Dedi (JURNAL BUANA, 2025)
This study aims to determine (1) Population growth and distribution in Sikakap Sub-district in 2018-2023. (2) Health facilities and infrastructure and accessibility of health facilities in Sikakap Sub-district. (3) Relationship between population growth and distribution to health facilities and infrastructure in Sikakap Sub-district. This research uses a quantitative description method with random data sampling. The methods used are population growth in the form of absolute, relative and average annual population growth and population projections using the exponential method. On population distribution using the population density method based on UU No. 56 of 1960 and building density using kernel density based on Permen No. 22 of 2021. On accessibility using the buffer (distance) and overlay (intersection) methods on Health Facilities and roads. The relationship is analyzed using correlation analysis and also the ratio of health facilities. The results showed that (1) absolute population growth in 2018 is 124 people, 2019 is 126 people, 2020 is -308 people, 2021 is 17 people, 2022 is 441 people and 2023 is -238 people, in relative population growth (%) in 2018 is 1.20%, 2019 is 1.21%, 2020 is -2.93%, 2021 is 0.17%, 2022 is 4.31% and 2023 is -2.23% with annual average growth in 2018-2023 is 0.11%. Population density in people/km2 in 2018 is 35.58, 2019 is 36.01, 2020 is 34.95, 2021 is 35.01, 2022 is 36.49 and 2023 is 35.71 and building density is "Very Low, Low, Medium, High, and Very High". (2) Health Facilities There are 31 units and the accessibility of facilities at the Puskesmas, clinic, posyandu, polindes, pharmacy and doctor / midwife practice is "Very Close, Close, Medium, Far, and Very Far". (3) Correlation Analysis is "Negative, Very Low, Strong, and Very Strong" and the Ratio of Health facilities at 1 puskesmas and pustu covers 10439 people.